'Boots for my Sancho': structural vulnerability among Latin American day labourers in Berkeley, California (2012)
This paper addresses the structural vulnerability of Latin American undocumented day labourers in Northern California, as it is expressed in conversations on street corners where they wait for work. The intimate aspects of migrant experience become exemplified in jokes about the Sancho - a hypothetical character who has moved in on a day labourer's family and who enjoys the money he sends home. Joking turns to more serious topics of nostalgia and tensions with family far away, elements that come together with the fears and threats of labour on the corner and affect the way day labourers see themselves. Sexuality is rearticulated in the absence of women and masculinity becomes enmeshed in the contingencies of unregulated work and long-term separation from the people the men support. Together, these elements result in the articulation of threat to the immigrant body itself, which is exemplified by anxieties over homosexual propositions on the corner.